An assessment of climate change science literacy and climate change pedagogical literacy of geography teachers in the Western Cape - Anyanwu, Raymond Ndubisi (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University 2015.